The Roads from Rio : Lessons Learned from Twenty Years of Multilateral Environmental Negotiations. - Chasek, Pamela (Taylor & amp ;, 2012)
At the 1992 United Nations Conference on Environment and Development, popularly known as the Rio Earth Summit, the world's leaders constructed a new "sustainable development" paradigm that promised to enhance environmentally sound economic and social development. Twenty years later, the proliferation of multilateral environmental agreements points to an unprecedented achievement, but is worth examining for its accomplishments and shortcomings. This book provides a review of twenty years of multilateral environmental negotiations (1992-2012). The authors have participated in most of t.